Determinación de las especies de Candida que colonizan el tracto respiratorio inferior en pacientes sintomáticos respiratorios (2012)
ABSTRACT: Colonization of the lower respiratory tract by Candida spp., is considered a prerequisite for the development of Candida infection in patients with risk factors. OBJECTIVE To determine the different Candida species colonizing the lower respiratory tract in patients with respiratory symptoms by bronchoalveolar lavages (BAL) assessment. MATERIALS AND METHODS We conducted a descriptive study, which analyzed 61 BAL samples from patients with respiratory symptoms. BAL samples were cultured on selective media including CHROMagar Candida™, tobacco agar and hypertonic Sabouraud agar; and identification was also performed by sugar assimilation method API 20C AUX®. Additionally, we determined the minimal inhibitory concentration (MIC) for fluconazole and voriconazole. RESULTS In 61 patients studied, we observed that 26 (42.6%) of them were colonized according to the following distribution: C. albicans (36.1%.), C. tropicalis (8.2%), C. krusei (3.3%), C. glabrata (3.3%), C. dubliniensis (4.9%), C. lusitaniae (1.6%) and other Candida species (6.6%). In addition, we found that some patients were colonized by more than one Candida species. Candida krusei and C. glabrata showed a diminished susceptibility or resistance to azoles, whereas C. albicans was 100% sensitive to these antifungals. CONCLUSIONS These results indicate that the frequency of the Candida spp., isolates in BAL from patients with respiratory symptoms is higher than that reported in other studies.